Instructional strategies that will promote literacy in an early childhood classroom for struggling readers (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
This article focuses on an issue that many teachers face with students when it comes to reading. At some point, perhaps very often, teachers in an early childhood setting will encounter students who struggle with reading. The focus of this article is to discuss strategies that will help and encourage struggling readers and assist in closing learning gaps in reading. The strategies discussed in this article are repeated readings, Reader’s Theatre, songs and poems.